2012
DOI: 10.1124/dmd.112.044719
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Proteomics of Transporter Expression in Brain Capillary Endothelial Cells Isolated from P-Glycoprotein (P-gp), Breast Cancer Resistance Protein (Bcrp), and P-gp/Bcrp Knockout Mice

Abstract: ABSTRACT:The objective of this study was to quantitatively examine the protein expression of relevant transporters and other proteins in the brain capillary endothelial cells isolated from wild-type mice and P-glycoprotein (P-gp), breast cancer resistance protein (Bcrp), and P-gp/Bcrp knockout mice. After the isolation of brain capillary endothelial cells, a highly sensitive liquid chromatography-tandem mass spectrometry method with multiple reaction monitoring was used to determine the quantitative expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
97
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 117 publications
(105 citation statements)
references
References 23 publications
8
97
0
Order By: Relevance
“…We addressed these questions by performing small-animal PET/MR experiments with 11 C-erlotinib without and with coinjection of a pharmacologic dose of unlabeled erlotinib (10 mg/kg) in wild-type and Abcb1a/b or Abcg2 knockout mice. Previous work has shown that Abcb1a/b (2/2) , Abcg2 (2/2) , and Abcb1a/b (2/2) Abcg2 (2/2) mice lack compensatory alterations in expression levels of other ABC and SLC transporters and are useful tools to study the effects of ABCB1 and ABCG2 on drug disposition (19). A potential limitation of using mice is their small blood volume, which prohibits arterial blood sampling, which is needed for quantitative analysis of PET data.…”
Section: Discussionmentioning
confidence: 99%
“…We addressed these questions by performing small-animal PET/MR experiments with 11 C-erlotinib without and with coinjection of a pharmacologic dose of unlabeled erlotinib (10 mg/kg) in wild-type and Abcb1a/b or Abcg2 knockout mice. Previous work has shown that Abcb1a/b (2/2) , Abcg2 (2/2) , and Abcb1a/b (2/2) Abcg2 (2/2) mice lack compensatory alterations in expression levels of other ABC and SLC transporters and are useful tools to study the effects of ABCB1 and ABCG2 on drug disposition (19). A potential limitation of using mice is their small blood volume, which prohibits arterial blood sampling, which is needed for quantitative analysis of PET data.…”
Section: Discussionmentioning
confidence: 99%
“…22 Proteomics analysis has identified secretory factors associated with adipogenesis in human adipose stromal vascular fraction cells and differentiated adipocytes. 23 Although proteomic methods have been used to characterize drug transporters and receptors at the BBB, 11,[24][25][26] the changes of BBB proteomes after DIO have not been shown previously. The proteins identified in our study are involved in a variety of cellular functions, cytoskeleton stability, stress response, vesicular transport, and energy metabolism ( Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…3D). Since Mrp2 and Mrp3 are unlikely to play a role in the blood-brain barrier of FVB mice, where they are not detectably expressed (Soontornmalai et al, 2006;Agarwal et al, 2012), this indicates that the combined deficiency of Bcrp1 and Mdr1a/1b results in higher brain accumulation of PhIP than the single deficiency of Bcrp1. Thus, not only Bcrp1 (Enokizono et al, 2008), but also Mdr1a/1b contributes to protection of the brain from PhIP, consistent with the observed modest in vitro transport of PhIP by Mdr1a (van Herwaarden et al, 2003).…”
Section: Discussionmentioning
confidence: 99%